Late clinical presentation of congenital adrenal hyperplasia in older children: findings from national paediatric surveillance. Issue 1 (16th September 2013) - Knowles, Rachel L; Khalid, Javaria M; Oerton, Juliet M; Hindmarsh, Peter C; Kelnar, Christopher J; Dezateux, Carol
Abstract : Objectives: To describe the clinical presentation and sequelae, including salt-wasting crises of newly-diagnosed congenital adrenal hyperplasia (CAH) in children aged over 1 year in a contemporary population without screening. To appraise the potential benefit of newborn screening for late-presenting CAH. Design: Active national surveillance undertaken in Great Britain prospectively from 2007–2009 through the British Paediatric Surveillance Unit. Setting: England, Wales and Scotland. Patients: Children first presenting aged 1–15 years with clinical features of CAH and elevated 17-hydroxyprogesterone. Results: Fifty-eight children (26 [45%] boys) aged 1–15 years were reported; 50 (86%) had 21-hydroxylase deficiency. Diagnosis was precipitated by secondary sexual characteristics (n=38 [66%]; median age 5.8 [IQR] 4.8, 7.6) years, genital virilisation (8 girls; 3.2 [IQR 1.3, 7.3] years) or an affected sibling (n=8; 10.0 [IQR 7.4, 13.3] years). At least 33 (57%) children had advanced bone age and 13 (30%) were obese (body mass index ≥95th centile). No child had experienced a salt-wasting crisis. Conclusions: In Great Britain, 30 children aged 1–15 years present annually for the first time with CAH. Older children frequently manifest prematurely advanced epiphyseal and pubertal maturation and genital virilisation, which are often irreversible and likely to have long-lasting consequences for adult health and wellbeing. Almost one-third of affected children are obese before commencing steroid therapy. Newborn screening offers the potential to avoid serious clinical manifestations in older children with unrecognised CAH; however, it may also detect some children who would otherwise remain asymptomatic and for whom the benefit from treatment is uncertain.